2012
DOI: 10.1002/mc.21935
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of crkl correlates with poor prognosis and cell proliferation in non‐small cell lung cancer

Abstract: Crk‐Like (CRKL) is an adapter protein that has crucial roles in multiple biological processes, including cell proliferation, adhesion, and migration. Amplification of CRKL gene was found in non‐small cell lung cancer (NSCLC). However, the expression pattern of CRKL protein and its clinical significance in human NSCLC have not been well characterized to date. In this study, expression of CRKL was evaluated in 131 NSCLC tissues by immumohistochemistry. CRKL protein was up‐regulated in the lung carcinomas compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
(30 reference statements)
3
32
1
Order By: Relevance
“…Overexpression of CRKL is found in NSCLC and is associated with poor tumor differentiation, AC, advanced p-TNM stage, high proliferation index and poor overall survival. In addition, overexpression of CRKL in cell lines promotes cell proliferation by facilitating cell cycle progression (56). In the current study, the CRKL protein level was not demonstrated to be significantly associated with clinical features such as gender, smoking history, clinical staging, EGFR status and ALK status.…”
Section: A B C Dcontrasting
confidence: 72%
“…Overexpression of CRKL is found in NSCLC and is associated with poor tumor differentiation, AC, advanced p-TNM stage, high proliferation index and poor overall survival. In addition, overexpression of CRKL in cell lines promotes cell proliferation by facilitating cell cycle progression (56). In the current study, the CRKL protein level was not demonstrated to be significantly associated with clinical features such as gender, smoking history, clinical staging, EGFR status and ALK status.…”
Section: A B C Dcontrasting
confidence: 72%
“…In recent decades, the biological roles of CCL20/CCR6 axis in progression and metastasis of gastric cancer were not well featured. In addition, CrkL acts as an adaptor protein to induce the intracellular signal transduction [8,9]. As reported, CrkL is also highly expressed in different cancer cells, such as gastric cancer, glioblastoma, hepatocellular carcinoma, and implicated in the aggressiveness and transformation of malignance [10,11].…”
Section: Introductionmentioning
confidence: 84%
“…CrkI is a more potent transforming gene than CrkII and CrkL in part because, like v-Crk, it lacks a C-terminal regulatory phosphorylation site (3). Overexpression of Crk and CrkL has been reported in several human cancers, including oral squamous cell carcinoma (5), ovarian carcinoma (6), colon cancer (7), lung cancer (8,9), breast cancer (10,11), gastric cancer (12), and glioblastoma (13,14). Reduced expression of either Crk or CrkL by RNA interference-mediated knockdown lowered the in vivo tumor formation of human ovarian (15), synovial sarcoma (16), glioblastoma (14), breast cancer (10), head and neck squamous cell carcinoma (17), and rhabdomyosarcoma (18) cell lines.…”
mentioning
confidence: 99%